Bifidobacterium breve Bif11 supplementation improves depression-related neurobehavioural and neuroinflammatory changes in the mouse. (15th May 2023) - Sushma, Gunuputi; Vaidya, Bhupesh; Sharma, Shikha; Devabattula, Geetanjali; Bishnoi, Mahendra; Kondepudi, Kanthi Kiran; Sharma, Shyam S.
Abstract: Gut dysbiosis has been closely linked to the onset and progression of several brain-related disorders such as depression. The administration of microbiota-based formulations such as probiotics helps restore healthy gut flora and plays a role in preventing and treating depression-like behavior. Therefore, we evaluated the efficacy of probiotic supplementation using our recently isolated putative probiotic Bifidobacterium breve Bif11 in ameliorating lipopolysaccharide (LPS)-induced depression-like behavior in male Swiss albino mice. Mice were fed orally with B. breve Bif11 (1 × 10 10 CFU and 2 × 10 10 CFU) for 21 days before being challenged with a single intraperitoneal LPS injection (0.83 mg/kg). Behavioral, biochemical, histological and molecular analysis were done with an emphasis on inflammatory pathways linked to depression-like behavior. Daily supplementation with B. breve Bif11 for 21 days prevented the onset of depression-like behavior induced by LPS injection, besides reducing the levels of inflammatory cytokines such as matrix metalloproteinase-2, c-reactive protein, interleukin-6, tumor necrosis factor-alpha and nuclear factor kappa-light-chain-enhancer of activated B cells. It also prevented the decrease of the brain-derived neurotrophic factor levels and neuronal cell viability in the prefrontal cortex of LPS-treated mice. Furthermore, we observed that gut permeability was reduced, there was an improved short-chain fatty acid profile and reduced gut dysbiosis in the LPS mice fed with B. breve Bif11. Similarly, we observed a decrease in behavioural deficits and restoration of gut permeability in chronic mild stress. Together, these results would help in deciphering the role of probiotics in the management of neurological disorders where depression, anxiety and inflammation are prominent clinical features. Highlights: Lipopolysaccharides administration in mice led to neurobehavioural deficits in the depression model. B. breve Bif11 supplementation produced an anti-inflammatory effect after lipopolysaccharides administration in mice. B. breve Bif11 supplementation improved the SCFA profile and reduced gut permeability in lipopolysaccharides-treated mice. Overall, these results demonstrate the neuroprotective potential of B. breve Bif11 in depression.